Analysis of the Relationship between Abuse of Power in Corruption Crimes and the Principles of Islamic Constitutional Law (A Fiqh Siyasah Review) - Sepriana Putri; Ismail Jalili; Sirajudin Sirajudin (Journal of Research in Social Science and Humanities, 2025)
Abuse of office leading to criminal acts of corruption is one of the greatest threats to governance and public welfare in Indonesia and other Muslim countries. From the perspective of Islamic constitutional law —which is a branch of fiqh siyasah (especially siyasah dusturiyah)—public office is understood not merely as administrative power, but as a mandate that must be carried out with the principles of justice (al-‘adl), responsibility (al-mas’uliyyah), and orientation towards the public interest (maslahah ‘ammah). Any form of abuse of power and authority in public office is seen as a betrayal of the trust given by Allah SWT and society. This article aims to analyse the relationship between abuse of office leading to corruption and violations of the principles of Islamic constitutional law, particularly within the framework of fiqh siyasah. This study uses a qualitative-normative approach with a literature review method of classical Islamic sources such as the works of Al-Mawardi and Ibn Taymiyyah, as well as contemporary literature discussing governance reform based on Islamic values. The data was analysed using a descriptive-analytical approach by comparing the concept of official responsibility in Islamic law and the provisions of positive Indonesian law, particularly Law No. 31 of 1999 and Law No. 20 of 2001 on the Eradication of Corruption. The results of the study show that abuse of office not only violates positive legal norms but also contradicts Islamic moral and spiritual principles that emphasise integrity, trustworthiness, and social justice. Fiqh siyasah offers a paradigm of governance oriented towards the welfare of the people with moral and institutional oversight through the concepts of hisbah and shura. Therefore, strengthening internal and external control mechanisms and internalising the values of fiqh siyasah into the national legal system are very important as efforts to prevent systemic corruption. Thus, the integration of Islamic constitutional law values and Indonesian positive law is expected to build clean, fair, and God-based governance.